Mapeamento dos Processos de Auditoria Financeira no Tribunal de Contas do Estado de Mato Grosso do Sul - Luísa Meinberg Cheade (2023)
Public organizations need to improve the provision of services by the public sector, especially in terms of transparency, reliability of information, the fight against corruption and control activities. This context includes financial audits carried out by the Courts of Auditors. This type of audit has been gaining ground in Brazil, not only because of the aforementioned agendas (including global ones), but also because of the demand from international organizations for the Courts of Auditors to adopt international standards for carrying out these audits in Brazil. Thus, the general objective of this study was to map the special-purpose financial audit processes carried out by the Independent Audit Commission (CAIN) of the Mato Grosso do Sul State Court of Auditors (TCE/MS), as an instrument for guaranteeing and monitoring the quality of the services provided. The proposed objective was achieved through from participant observation based on the use of qualitative and quantitative methods. Considering the complexity of understanding each process and sub-process of the work, given the minutiae of the activities involved, the financial audit macro-process was designed based on the division of its phases (planning - identification and assessment of risks; execution - responses to risks; and reporting - forming an opinion). It was possible to identify that the financial audit macro-process can be divided into five processes and three sub-processes. Although these workflow diagrams are based on the practice of the TCE/MS, they can be used by any of the 21 Courts of Auditors that carry out special-purpose financial audits in the country.